The effect of problem-based learning (PBL) on different academic abilities on critical thinking of grade XI students on coordination system material - Ria Mayasari; Siti Ramdiah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Scientific actions related to facts and everyday problems are needed in the biology learning process to train students' thinking skills. Thinking skills are useful for facing the challenges of education and technological developments in the 21st century. However, these conditions are not optimal, especially critical thinking skills for different academic abilities. The purpose of this study was to determine the effect of the PBL model on different academic abilities on the critical thinking of class XI students on the coordination system material. This quasi-experimental research was conducted on students of class XI IPA 1 at SMAN 10 Banjarmasin and class XI IPA 3 at SMAN 12 Banjarmasin. The sample of the upper academic ability is 26 students, and the lower academic ability is 28 students. The instrument used is an essay through pretest and posttest in the experimental class and control class. Data were analyzed using Anacova after the data fulfilled the normality and homogeneity tests. The results of the analysis show that there is an influence of the PBL learning model on critical thinking in students of different academic abilities, where the class F value is 91.84 with a p value of 0.000 or less than 0.05. The academic F score is 8.26 with a p value of 0.006 or less than 0.05. This learning model can be a solution to produce graduates who are competent in critical thinking.Abstrak Tindakan-tindakan ilmiah yang berkaitan dengan fakta dan masalah sehari-hari diperlukan dalam proses belajar biologi untuk melatihkan kemempuan berpikir siswa. Keterampilan berpikir berguna untuk menghadapi tantangan pendidikan dan perkembangan teknologi abad 21. Namun kondisi ini belum maksimal terutama keterampilan berpikir kritis pada kemampuan akademik berbeda. Tujuan penelitian ini yaitu mengetahui pengaruh model PBL pada kemampuan akademik berbeda terhadap berpikir kritis siswa kelas XI pada materi sistem koordinasi. Penelitian quasi eksperimen ini dilaksanakan pada siswa kelas XI IPA 1 SMAN 10 Banjarmasin dan kelas XI IPA 3 SMAN 12 Banjarmasin. Sampel kemampuan akademik atas berjumlah 26 siswa, dan akademik bawah 28 siswa.  Instrumen yang digunakan berupa essay melalui pretest dan postest pada kelas eksperimen dan kelas kontrol. Data dianalisis menggunakan Anacova setelah data memenuhi uji normalitas dan homogenitas. Hasil analisis menunjukkan bahwa terdapat pengaruh model pembelajaran PBL terhadap berpikir kritis pada siswa kemampuan akademik yang berbeda, dimana nilai F hitung kelas sebesar 91,84 dengan nilai p 0,000 atau kurang dari 0,05. Nilai F hitung akademik sebesar 8,26 dengan nilai p 0,006 atau kurang dari 0,05. Model pembelajaran ini bisa menjadi solusi untuk menghasilkan lulusan pendidikan yang kompeten dalam berpikir kritis.